You Can't Take It With You, 1962 #01 - Missouri Southern State University (1962)
David Charron, Pam Plummer, Nelson Clark, Steve Garrison, Richard Showalter, Barbara Stone, Karalee Pearson, John Koeneman, Mike Boyington, Ann Francisco, David Lightdourn